Trabajo social con comunidades. Pastor Seller, E. (2015). Madrid: Universitas ISBN 978-84-799-1451-6 - Antonia Picornell Lucas (Sociedad Iberoamericana de Pedagogía Social, 2016)
Pastor Seller, E. (2015). Madrid: Universitas ISBN 978-84-799-1451-6